Efek Ketergantungan Remaja K-Popers Terhadap Media Sosial di Kota Palu - Muhammad Khairil; Muhammad Isa Yusaputra; Nikmatusholeha . (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2019)
Korean culture was introduced in Indonesia since early 2000s through dramas, movies and musics. However, the Korean fever lasts about a decade. During that period, this commodity became better known as Korean Pop or K-Pop where teenagers who became the biggest consumers of this commodity known as K-Popers. K-Popers can not be separated from the technology development and the use of social media. This study is carried out using three aspects (frequency, duration and attention) of media exposure theory. The purpose of this study is to understand the effect of K-Pop information access on the teenager’s social media dependency. This study is utilizing explanatory quantitative approach based on survey to 71 10th grade students of Unified Model High School of Madani Palu. Obtained data are analyzed using linear regression method. The results of the study shows that the effect of the frequency, duration and attention aspects in the population’s access to K-Pop informations to the teenager’s social media dependency of Palu City is at 77,1%. Thus, it is concluded that there is a direct effect on K-Pop information access to the teenager’s social media dependency. The substance provided by this study offers new point of view on the educational approach of social media usage in Palu City to improve the self-control and selective behaviour of social media usage.